Kajian Perilaku Petani Bawang Daun (Allium Fistulosum L.) dalam Mereduksi Risiko sebagai Upaya Meningkatkan Produktivitas Usahatani di Desa Linonggasay - Mursal Junus (Journal of Student Research, 2025)
The purpose of this study was to determine the amount of income and the amount of risk of Scallion farming and to describe the behavior of farmers in reducing the risk of onion farming in Konawe Regency. The study was conducted in 2023 at the onion production center in Linonggasay Village, West Wonggeduku District with a total sample of 20 farmers. The analysis used was income analysis and descriptive analysis of the risk level using the variation coefficient (%). The results showed that the average net income was IDR 12,788,000 per planting season. Scallion farming is included in the category of farming with a risk of less than 0.5, namely the use of equipment (0.05), the use of pesticides (0.13), and the use of labor in fertilization (0.32), while the rest have moderate risks, namely harvest labor (0.51), planting labor (0.59), seeds (0.64), fertilizer (0.72), and processing (0.90) and none in the high risk category. Some of the farmer behaviors carried out to reduce risk include: buying seeds from saprodi kiosks, controlling plant pests using chemical fertilizers, using recommended planting distances, utilizing labor from outside the village, and in the event of failure, taking savings to meet family needs.